A case report: Does the ulcer belong to esophageal carcinoma or HIV?. Issue 49 (December 2017) - Jia, Ning; Tang, Yanping; Li, Yang; Gan, Yongkang
Abstract: Rationale: The deep-rooted pathogenesis of the human papilloma virus (HPV) infection is still uncertain and argumentative. As we know, a lot of cases of esophageal infections, such as esophageal squamous cell carcinoma (ESCC) and esophageal squamous papilloma (ESP), associated with HPV are reported. However, primary esophageal ulcer infection associated with HPV is unusual. Patient concerns: This case is different from the other reports associated with HPV due to the patient's favorable prognosis. Diagnoses: We present a case of a man diagnosed in the Gastroenterology Department of Tianjin Hospital of Integrated Traditional Chinese and Western Medicine, which presented a deep and big esophageal ulcer with irregular borders caused by type 16 HPV infection. Interventions: The esophageal ulcer was treated with vidarabine monophosphate treatment. Outcome: The esophageal ulcer was cured. Lessons: We could put forward the diagnostic criteria available for diagnostic guidelines and 2 hypotheses that could possibly prevent esophageal carcinoma from happening.